Association Between Chronic Medical Conditions and Acute Perinatal Psychiatric Health-Care Encounters Among Migrants: A Population-Based Cohort Study. (December 2020) - McKnight, Anthony; Vigod, Simone N.; Dennis, Cindy-Lee; Wanigaratne, Susitha; Brown, Hilary K.
Objectives: To examine the relationship between prepregnancy chronic medical conditions (CMCs) and the risk of acute perinatal psychiatric health-care encounters (i.e., psychiatric emergency department visits, hospitalizations) among refugees, nonrefugee immigrants, and long-term residents in Ontario. Methods: We conducted a population-based study of 15- to 49-year-old refugees ( N = 29, 189), nonrefugee immigrants ( N = 187, 430), and long-term residents ( N = 641, 385) with and without CMC in Ontario, Canada, with a singleton live birth in 2005 to 2015 and no treatment for mental illness in the 2 years before pregnancy. Modified Poisson regression was used to estimate the relative risk of a psychiatric emergency department visit or hospitalization from conception until 1 year postpartum among women with versus without CMC, stratified by migrant status. An unstratified model with an interaction term between CMC and migrant status was used to test for multiplicativity of effects. Results: The association between CMC and risk of a psychiatric emergency department visit or hospitalization was stronger among refugees (adjusted relative risk [aRR] = 1.87; 95% confidence interval [CI], 1.36 to 2.58) compared to long-term residents (aRR = 1.39; 95% CI, 1.30 to 1.48; interaction P = 0.047). The strength of the association was no different in nonrefugee immigrants (aRR = 1.26; 95% CI, 1.05 to 1.51) compared to long-term residents (interaction P = 0.45). Conclusion: Our study identifies refugee women with CMC as a high-risk group for acute psychiatric health care in the perinatal period. Preventive psychosocial interventions may be warranted to enhance supportive resources for all women with CMC and, in particular refugee women, to reduce the risk of acute psychiatric health care in the perinatal period.